Coherent Particle Acceleration on a Nanophotonic Chip - Brückner, Leon; Chlouba, Tomas; Shiloh, Roy; Kraus, Stefanie; Litzel, Julian; Hommelhoff, Peter (2024 37th International Vacuum Nanoelectronics Conference (IVNC), 2024)
Dielectric Laser Acceleration (DLA) offers a path-way to miniaturized particle accelerators capable of generating high-energy, ultrashort electron bunches. A typical DLA nanostructure comprises two rows of silicon pillars illuminated by an infrared laser pulse, creating an oscillating nearfield mode. Electrons that are phase-matched to this mode gain energy as they pass through the channel between the pillars. Transverse particle confinement is achieved by exploiting the transverse forces exerted by the nearfield, facilitating beam transport over considerable distances. By combining transverse confinement and a tapering of the structure period for continual phase-matching, acceleration over long distances is made possible. Experimental results demonstrate successful capture, confinement, and acceleration of electron bunches, with a notable energy gain of 12.3 keV, or 43% increase compared to the starting energy, in a 500 µm long acceleration structure. Further refinement and extension of interaction length hold promise for enabling applications such as high-energy electron imaging and diffraction as well as bio-medical applications. Exploration of diverse dielectric materials and excitation wavelengths may yield even higher acceleration gradient